Pengaruh Penggunaan Aplikasi BUPIN terhadap Peningkatan Hasil Belajar Siswa Madrasah Aliyah Plus Taruna Islam Al-Kautsar Kraksaan Probolinggo - Rizki Hadi Suhendra; Abdul Aziz Wahab; Ahmad Khumaidi (ISLAMIKA, 2023)
This research was conducted to determine whether the implementation of the BUPIN (Interactive Learning Book) application can improve student learning outcomes. In this case, the researcher chose a comparative quantitative approach. The population selected by the researcher consists of all 62 students of MA Plus Taruna Islam Al-Kautsar in the academic year 2022/2023. The simple random sampling technique was used to determine the sample members, and the researcher selected 21 students from class X. The data collected by the researcher consisted of mid-term and final exam scores. The data were analyzed using one-way ANOVA, and the SPSS version 16.0 application was used to assist in data analysis. From the results of the analysis, the researcher obtained a significant value of less than 0.05 (0.000 < 0.05). Therefore, it can be concluded that the use of the BUPIN (Interactive Learning Book) application can improve student learning outcomes.